2012
DOI: 10.1007/s00253-012-3957-8
|View full text |Cite
|
Sign up to set email alerts
|

Red mold, diabetes, and oxidative stress: a review

Abstract: Type 2 diabetes is a major health concern and a rapidly growing disease with a modern etiology, which produces significant morbidity and mortality. The optimal management of type 2 diabetes aims to control hyperglycemia, hypertension, and dyslipidemia to reduce overall risks. Diabetes and its complications usually develop as oxidative stress increases. Monascus-fermented rice, also called red mold rice or red mold dioscorea are used in China to enhance food color and flavor. Red mold-fermented products are pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 81 publications
0
22
0
1
Order By: Relevance
“…It is known that significant increase in oxidative stress is observed in obese subjects [15][16][17]. Hyperglycemia, fundamental abnormality found in diabetes, can also induce oxidative stress [17][18][19][20]. Therefore, the obese and diabetic conditions of KK-A y mice resulted in oxidative stress to produce more lipid hydroperoxides than those found in normal ICR mice (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that significant increase in oxidative stress is observed in obese subjects [15][16][17]. Hyperglycemia, fundamental abnormality found in diabetes, can also induce oxidative stress [17][18][19][20]. Therefore, the obese and diabetic conditions of KK-A y mice resulted in oxidative stress to produce more lipid hydroperoxides than those found in normal ICR mice (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have observed elevated levels of oxidative stress markers in patients with T2D [20,21]. Therefore, the imbalance between oxidant and antioxidant systems is also involved in the pathogenesis of T2D and its complications [22][23][24]. Recent data demonstrates that oxidative stress influences cell-cycle regulators in β cell proliferation and neogenesis [25].…”
Section: Oxidative Stress and Autoimmunitymentioning
confidence: 99%
“…Lee et al (2011) reported that yellow pigment, Monascin, was able to improve insulin sensitivity through serine/threonine protein kinases pathway by stabilizing PPAR-γ structure, preventing its phosphorylation, and inhibiting c-Jun N-terminal kinase activation. Shi et al (2012) suggest that the Monascin has a therapeutic potential on diabetes and diabetes-associated oxidative stress complications. Higher level of MFDS suspension has higher contents of phenolic and pigments which might be resulted higher effectiveness in lowering blood glucose.…”
Section: Resultsmentioning
confidence: 99%
“…During solid state fermentation, Monascus produces various secondary metabolites primarily pigments and monacolines with various bioactivities, and the fermented products showed possitive health effects (Chang et al, 2006;Chen et al, 2006;Lin et al, 2008;Shi et al, 2010;Shi et al, 2012).…”
Section: Monascus-fermentedmentioning
confidence: 99%